2019
DOI: 10.1111/ene.13920
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial injury in transient global amnesia: a case‐control study

Abstract: Background and purpose Elevation of cardiac troponin (cTn), a sensitive biomarker of myocardial injury, is frequently observed in severe acute neurological disorders. Case reports suggest that cardiac dysfunction may also occur in patients with transient global amnesia (TGA). Until now, no study has systematically assessed this phenomenon. Methods We performed a case‐control study using data of consecutive patients presenting with TGA from 2010 to 2015. Multiple logistic regression analysis accounting for age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…TGA is often preceded by an emotionally or physically stressful event leading to focal metabolic disturbance within the hippocampus, which is another region involved in the central autonomic control of the heart [ 44 ]. In two recent retrospective cohort studies, the prevalence of a cardiac involvement in TGA patients was investigated [ 45 , 46 ]. Approximately 25% of TGA patients presented with elevated hs-cTn levels.…”
Section: Troponin and Other Neurological Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…TGA is often preceded by an emotionally or physically stressful event leading to focal metabolic disturbance within the hippocampus, which is another region involved in the central autonomic control of the heart [ 44 ]. In two recent retrospective cohort studies, the prevalence of a cardiac involvement in TGA patients was investigated [ 45 , 46 ]. Approximately 25% of TGA patients presented with elevated hs-cTn levels.…”
Section: Troponin and Other Neurological Diseasementioning
confidence: 99%
“…Approximately 25% of TGA patients presented with elevated hs-cTn levels. After multivariable adjustment, the diagnosis of TGA was associated with a higher risk of hs-cTn elevation than diagnosis of transient ischemic attack (TIA), migraine with aura or acute vestibular syndrome [ 46 ]. Altogether, these correlations indicate that mechanisms similar to those described for the ‘Stroke-Heart syndrome’ are involved in the occurrence of myocardial injury after acute neurological conditions.…”
Section: Troponin and Other Neurological Diseasementioning
confidence: 99%
“…For Takotsubo cardiomyopathy, that might share pathophysiological mechanisms with TGA [5,6], it has been reported that it can occur in the context of natural disasters like e. g. earthquakes [7]; the first cases in the context of Covid-19 have been published recently [8][9][10].…”
mentioning
confidence: 99%
“…Taking all together, intense emotional or physical stress as a frequent precipitating event with excessive sympathetic activation might elicit cardiac diastolic and/or systolic output dysfunction resulting in brain hypoperfusion compromising susceptible brain structures such as the hippocampus. This possible pathophysiology of TGA and ischemic amnesia is supported by a recently published report presenting evidence that the likelihood of myocardial injury in patients with TGA was twofold higher compared to patients with transient ischemic attack [9]. In another recent study nearly 9% of TGA patients had elevated levels of high sensitive troponine T, suggesting myocardial injury [10].…”
Section: Discussionmentioning
confidence: 75%